Impact of service strategy on customer satisfaction of the rail management in Malaysia - Yusoff, Mohd Zaki; Razalli, Mohd Rizal (2012)
This paper project is evaluates the level of customer satisfaction among the Malayan railways KTMB passengers. The factors with to evaluate the level of customer satisfaction are the on-line services, fare charging practices, customer services and advertisement.The dependent variable which measured is customer satisfaction. A quantitative approach with a multiple regression analysis was deployed to study the relationship between the independent variables and dependent variable. The factors such as the fare charging practices and customer services though show a positive relationship with customer satisfaction, but the relationship is not significant. However, the passengers are very concern about the on-line services, and advertisement used to communication with them to improve the on-line services, and advertisement in other deliver customer satisfaction continuously.